“Diseño y producción de un canal de TV en línea para el Ministerio de Cultura.” - Garcia Vivar, Rafael Carlos (2021)
The Ministry of Culture´s online TV channel, cultura24.tv, is a platform destined for the distribution of audiovisual content specialized in art and culture via web. It´s way of operation is based on the digital convergence of two languages: the television and the internet, furthermore proposing a new perspective on the way in which audiovisuals are delivered to the audience. In this document you will find a descriptive review of the operation, starting from the project stage, showing the development process of an online TV channel and finally explaining the various components and stages that it has, contributing to the development of similar initiatives.